TOXICOLOGICAL AND PHARMACOLOGICAL CHARACTERISTICS OF EXCIPIENTS OF DRUG PRODUCTS OF TORASEMIDE - D. Yu. Ivkin; A. A. Teslev; A. S. Dziuba; A. S. Ivkina (Разработка и регистрация лекарственных средств)
Information on the toxicological and pharmacological characteristics of the main excipients used in the formulation of torasemide (sodium croscarmellose, microcrystalline cellulose, magnesium stearate, pregelatinized corn starch, silica, mannitol) is presented in the article.